TRAFFICKING PRESPEKTIF HUKUM PIDANA - Dian Novita Dian Novita (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
Abstract: Trafficking is a classic matter that has been existed since the establishment of human culture. The major cause of the trafficking is the lack of information about trafficking, poverty and the law level of education and skill of people, specifically villagers. To fight against trafficking, the government needs to accelarate the education and skill quality and cooperate with other countries. Besides, it is important to provide a sufficient law device for international scale in order to drag feet the trafficking network. Furthermore, trafficker must be punished with heavy penalties and the victim must be protected properly. Key Words: Trafficking, hukum pidana, pelaku dan korban